دور التسويق الإجتماعي في تعزيز الصورة الذهنية للمنظمات غير الربحية " د راسة حالة الجمعية الخيرية الوطنية لكافل اليتيم فرع سوق أهراس - محمد أنيس قواسمية.; عماد سيحمدي . (My University, 2022)
The study aimed to identify the role and importance of social marketing, as well as the extent of its effectiveness and impact in enhancing and improving the mental image of the National Charitable Association, Kafeel Orphan - Souk Ahras Branch - as one of the non-profit organizations of charitable and social character, and this study relied on the descriptive analytical approach to the opinions of the heads of the association And its affiliates in the state of Souk Ahras, where the study dealt with the independent variable that is represented in social marketing with its seven dimensions of (social product, social price, social distribution, social promotion, physical evidence, operations, participation), and a dependent variable represented in the mental image and its three dimensions (the image Subjective image, desired image, perceived image), for the intended or targeted sample, and in order to identify the objectives of the study, a questionnaire was formulated for the purpose of collecting information from the target sample, and in the end the study reached a set of results, the most important of which are: Social marketing has a prominent role and influence in enhancing and improving the mental image, and there is also a direct relationship between them, as there is a strong and direct relationship between the two dimensions of operations and participation with the mental image, and there is an influential role for the following dimensions (social product, physical evidence, participation, operations) In improving the mental image, and there is no contribution or effectiveness to the social price dimension, the social promotion dimension, and the social distribution dimension among the study sample. Finally, the study suggests focusing and increasing interest in social marketing because it has an effective role and as a mechanism to enhance the mental image of the National Charitable Association, the Orphan Sponsor, as a non-profit organization .......................................... هدفت الدراسة الى التعرف على دور و اهمية التسويق الإجتماعي و كذا مدى فاعليته و تاثيره في تعزيز و نحسين الصورة الذهنية عن الجمعية الخيرية الوطنية كافل اليتيم فرع سوق اهراس كاحد المنظمات الغير ربحية ذات الطابع و الصفة الخيرية و الاجتماعية و اعتمدت هذه الدراسة على المنهج الوصفي التحليلي لاراء رؤساء الجمعية و منتسبينها بولاية سوق اهراس ، حيث تناولت الدراسة المتغير المستقل و الذي تمثل في التسويق الاجتماعي بأبعاده السبعة المتمثلة في المنتج الاجتماعي ، السعر الاجتماعي، التوزيع الاجتماعي ، الترويج الاجتماعي ، الدليلي المادي ، العمليات ، المشاركة ، و المتغير تابع تمثل في الصورة الذهنية و ابعادها الثلاثة الصورة الذاتية ، الصورة المرغوبة، الصورة المدركة ، لعينة المقصودة او المستهدفة و بغية الوقوف على اهداف الدراسة ثم صيغة استبيان لغرض جمع المعلومات من العينة المستهدفة ، و في الاخير توصلت الدراسة الى مجموع من النتائج و من اهمها: يوجد للتسويق الاجتماعي دور مهم و تاثير بارز في تعزيز و تحسين الصورة الذهنية و هناك ايضا علاقة طردية بينهما، كما انه هناك علاقة قوية و طردية بين بعدي العمليات و المشاركة مع الصورة الذهنية و ههناك ايضا علاقة طردية بينهما و تقترح الدراسة في الاخير بتركيز و زيادة الاهتمام بالتسويق الاجتماعي لما له له من دور فاعل و كآلية لتعزيز الصورة الذهنية لجمعية الخيرية الوطنية كافل اليتيم كمنظمة غير ربحية